A Triple-band Dipole Antenna with 0.92 GHz AMC-HIS - Abu, Maisarah; A. Rahim, Mohamad Kamal; Suaidi, Mohamad Kadim; Mohd Ibrahim, Imran; Mohd Nor, Norazura (2010)
A triple-band dipole antenna integrated with 0.92 GHz Artificial Magnetic Conductor (AMC) is presented. The AMC structure is called a highimpedance surface (HIS) structure and is useful as a ground plane to the dipole antenna. This structure can be used to prevent the degradation of tag and antenna performance caused by the conductive materials (metal objects) and to increase the antenna gain. This paper begins by investigating the parameters in AMC design such as a patch and gap size. The AMC is characterized by the frequency where the phase of the reflection coefficient is zero degrees and has reflected wave in-phase with the incident wave.